Statistics Application Socialization to Analyze Student Learning Outcomes Evaluation Data for Teachers - Nyoman Sridana; Amrullah Amrullah; Hapipi Hapipi; Deni Deni; Nourma Nourma (Unram Journal of Community Service, 2022)
This service is based on the competency standard of statistical knowledge and the evaluation of teachers is still low, so teachers need socialization regarding the application of statistics to analyze data on evaluating student learning outcomes. According to Law No. 15 of 2005, the development of the teaching profession can be carried out by increasing scientific knowledge both in the field of teaching materials and in the field of pedagogy. The method used in this service activity is mentoring including lectures, questions, answers, and presentation assignments in face-to-face, and online forms. This service activity is arranged in four stages, of which one stage is carried out face-to-face and three stages are carried out online. Face-to-face activities are carried out using lecture and question-and-answer methods. while online activities are carried out with FGDs, questions and answers, and presentations. The expected outcome after this service is that teachers are proficient in using statistical application programs in analyzing valid and significant evaluation data on student learning outcomes.